2019
DOI: 10.1108/mf-03-2018-0121
|View full text |Cite
|
Sign up to set email alerts
|

A student-managed investment fund course design structure

Abstract: Purpose The purpose of this paper is to provide a detailed framework of goals, processes and solutions that can serve as a starting point for instructors in designing their own student-managed investment fund (SMIF) course experience that is relevant for all undergraduate business majors. Design/methodology/approach The design is suitable for a wide audience without prior equity investment expertise, lead to equity portfolio management competency and concentrate heavily on the understanding of the elements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This viewpoint is substantiated by Rajasulochana et al (2019), who observed that a student-managed investment course would strengthen the students’ learning and help them be up to date with stock market information. Phillips et al (2019) assert that a course structure would help the students as it would create a motivating environment for learning. One of the respondents felt it would increase the possibility of selecting only the academically proficient students, thereby overlooking those who are interested in finance and are dedicated:E- “So we cannot say how fair that selection process is, because people with high CGPA scores would get into the Fund because they are meritorious academically.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This viewpoint is substantiated by Rajasulochana et al (2019), who observed that a student-managed investment course would strengthen the students’ learning and help them be up to date with stock market information. Phillips et al (2019) assert that a course structure would help the students as it would create a motivating environment for learning. One of the respondents felt it would increase the possibility of selecting only the academically proficient students, thereby overlooking those who are interested in finance and are dedicated:E- “So we cannot say how fair that selection process is, because people with high CGPA scores would get into the Fund because they are meritorious academically.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Special Issue No. 1: traditional SIM programs: From the University of Tennessee at Chattanooga, (Student Managed Funds – a panel discussion), submitted by Hunter Holzhauer, Arindam Bandopadhyaya, Deborah Harrell, Timothy A. Krause and Judson Russell (2020). From Austin Peay State University, (A student-managed investment fund course design structure), submitted by Michael D. Phillips, John X. Volker and Susan Cockrell (2020). From Truman State University (Variation in the structure and administration of student-managed funds), submitted by Charles M. Boughton and Katherine L. Jackson (2020). From Whitworth University, (Student investment groups: enhancing the liberal arts experience), submitted by Brian D. Bergquist, Dawn L. Keig and Timothy J. Wilkinson (2020). From Western Illinois University, (Structuring stock investment funds with a limited number of qualified students), submitted by David Deboeuf (2020). From California State University Long Beach, (The learning experience continues: two decades and counting for the CSULB’s SMIF program), submitted by Peter A. Ammermann, Pia Gupta and Yulong Ma (2020). From Stonehill College, (A five-year retrospective on an undergraduate SIMF program), submitted by Michael G. Mullen and Debra Salvucci (2019). From the University of Utah, (The essence of investing: experiential education with a student-run portfolio), submitted by Elizabeth Tashjian (2020). From the University of Connecticut, (Student managed fund (SMF) at the University of Connecticut: history, purpose, performance and the future), submitted by Chinmoy Ghosh, Paul Gilson and Michael Rokatomavo (2020). From the University of Arkansas, (Rebsamen investment fund integration in finance education), submitted by Samar Ashour, Craig G. Rennie and Sergio Santamaria (2020). From Memorial University in Newfoundland, Canada, (Confessions of a faculty advisor: development of a student managed investment fund program under constraints), submitted by Erin Oldford (2020).…”
mentioning
confidence: 99%
“…From Austin Peay State University, (A student-managed investment fund course design structure), submitted by Michael D. Phillips, John X. Volker and Susan Cockrell (2020).…”
mentioning
confidence: 99%